Base modifications affecting RNA polymerase and reverse transcriptase fidelity. Issue 11 (10th May 2018) - Potapov, Vladimir; Fu, Xiaoqing; Dai, Nan; Corrêa, Ivan R; Tanner, Nathan A; Ong, Jennifer L
Abstract: Ribonucleic acid (RNA) is capable of hosting a variety of chemically diverse modifications, in both naturally-occurring post-transcriptional modifications and artificial chemical modifications used to expand the functionality of RNA. However, few studies have addressed how base modifications affect RNA polymerase and reverse transcriptase activity and fidelity. Here, we describe the fidelity of RNA synthesis and reverse transcription of modified ribonucleotides using an assay based on Pacific Biosciences Single Molecule Real-Time sequencing. Several modified bases, including methylated (m 6 A, m 5 C and m 5 U), hydroxymethylated (hm 5 U) and isomeric bases (pseudouridine), were examined. By comparing each modified base to the equivalent unmodified RNA base, we can determine how the modification affected cumulative RNA polymerase and reverse transcriptase fidelity. 5-hydroxymethyluridine and N 6 -methyladenosine both increased the combined error rate of T7 RNA polymerase and reverse transcriptases, while pseudouridine specifically increased the error rate of RNA synthesis by T7 RNA polymerase. In addition, we examined the frequency, mutational spectrum and sequence context of reverse transcription errors on DNA templates from an analysis of second strand DNA synthesis.